Cough as a symptom of respiratory infection or a rare cardiological pathology in an infant - Chanas, Anna; Obsznajczyk, Klaudia; Kucińska, Beata; Werner, Bożena (Pediatria Polska - Polish Journal of Paediatrics, 2023)
Congenital coronary artery anomalies are rare and represent 0.24–0.46% of all congenital heart defects. The most common is an anomaly in which the left coronary artery arises from the pulmonary artery (ALCAPA), also known as a Bland-White-Garland syndrome. Nonspecific symptoms typically appear at 2–3 months of age. We present the case of a 10-week-old boy admitted to the hospital due to cough and dyspnea, with suspicion of a respiratory tract infection with no clinical improvement after standard therapy. The chest X-ray revealed cardiomegaly. The electrocardiogram showed signs of anterolateral infarction. Echocardiography revealed signs of dilatated cardiomyopathy and color Doppler was of great value in establishing a final diagnosis. After confirming the diagnosis of ALCAPA in computed tomography angiography, the patient was operated on, with a good outcome.